(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Former hydrocarbons importers will likely be the biggest losers from the power shift, since renewable power is believed to worsen security problems and geopolitical conflicts relating to crucial materials and cybercrime. Many of the publications examined had the following flaws: an inability to explain the term "geopolitics"; an unfounded assumption that there has not been much published in the region previously; insufficient use of current forecasting, circumstance, or futurist methods; a lack of acknowledgment of the topic’s complexities; a lack of theorizing Most writers do not differentiate between the geopolitical concerns connected with various wind and solar, and only a few make a clear distinction between the demographics of the transitional period and the demographics of a world after the energy transition. Only a tiny percentage of the literature is devoted to the demise of old fossil fuel powers, whereas key materials and cybersecurity get hugely disproportionate amounts of attention. There is an over there on oil companies and an insufficient attention to nations that depend significantly on coal that among periodicals that do mention the collapse of carbon fuels. The scope for improvement in India’s energy system is vast.